Effects of Service Quality on Taxpayer Satisfaction: A Case of a Client Relationship Management Program - Hapala, Enoch Ambitious; Kaunda, Stan Gottlieb; Lipunga, Andrew Munthopa (JABE (JOURNAL OF ACCOUNTING AND BUSINESS EDUCATION), 2024)
The paper examines the effects of service quality on the satisfaction of taxpayers using the service quality (SERVQUAL) framework. Data was collected using a questionnaire and was analyzed using a multiple regression model. The results indicate that only 49% of the variations in taxpayer satisfaction can be explained by service quality (R2 = 0.4892). Further, the results indicate that while all five dimensions of service quality have a positive effect on taxpayer satisfaction, four (reliability, assurance, tangibility, and empathy) are statistically significant (p-values < 0.05) on the other hand, responsiveness is statistically insignificant (p-values > 0.05). The results imply that tax authorities should not overly focus on service quality to enhance taxpayer satisfaction as it accounts for only half of the variations. The other factors may need to be identified and implemented together with service quality. Concerning service quality, the focus of the tax authorities should be placed on reliability, assurance, tangibility, and empathy.